Preparation and immunological study of Ichthyophthirius multifiliis β-tubulin DNA vaccine in grass carp (Ctenopharyngodon idella) - Jiazheng Ye; Fangling Liu; Siqi Ren; Zhuo Cai; Kejing Huang; Xinrui Wu; Yurui Lin; Wanqing Tong; Qianhui Li; Shanjian Zheng (Aquaculture Reports)
Grass carp, a common aquatic species in China, suffer significant annual losses due to infection by the parasitic ciliate Ichthyophthirius multifiliis (Ich), thus necessitating effective prevention and control measures. In the present study, the Ich β-tubulin gene was cloned and inserted into the eukaryotic expression vector pVAX1 plasmid to construct the Ich β-tubulin DNA vaccine (pVAX1-Bt). After two doses of the pVAX1-Bt vaccine, the relative percentage survival (RPS) reached 70.0 %, whereas the RPS after 2 doses of pVAX1 reached 10.0 %. The β-tubulin antibody, specific antibody IgM, and immune enzymes (MDA, SOD, CAT, ACP, AKP, and cortisol) were tested over13 weeks. The findings revealed a significant enhancement in the vaccinated fish compared to their unvaccinated counterparts, indicating that the vaccine can activate the humoral immune pathway and non-specific immunity in fish, thereby promoting the production of specific antibodies and memory B cells. Collectively, these results indicate that the Ich β-tubulin DNA vaccine has potential in treatment of Ich infection (ichthyophthiriasis).